DIVERSITY OF SEAWEED SPECIES AROUND LY SON ISLAND, QUANG NGAI PROVINCE - Duy, Đỗ Anh; Hướng, Trần Văn; Tuấn, Bùi Minh; Hiếu, Nguyễn Văn; Mai, Nguyễn Thị; Hồng, Đặng Diễm (Hue University Journal of Science: Natural Science, 2019)
Ly Son is an island district located in the northeast of Quang Ngai province, has an important strategic position (the A10 point to baselines) with a great potential for socio-economic development combined with national security. The biological resources in coastal areas surrounding the Ly Son island are relatively abundant and diverse. The results of seaweed resources from surveys for two years (2017 - 2018) in the Ly Son island have identified 143 seaweed species belonging to 36 families, 18 orders of 4 seaweed phylums. Specifically, Rhodophyta had the highest identified species with 67 species; followed by Ochrophyta (39 species) and Chlorophyta (36 species); the lowest was Cyanobacteria (1 species). The study have also recorded 60 seaweed species of high economic value; 2 species of endangered (EN) and 1 species of vulnerable (VU). The average biomass of seaweed was 3,312 ± 436 g/m2. Some groups of economic seaweed species distributing with high biomass such as Sargassum, Gracilaria, Hydropuntia, Caulerpa, Gelidiella have important implications for human life in the Ly Son island.